Application of Molecular Biology for Identification of Virus Resistance Gene in Melon - Budi Setiadi Daryono (Universitas Gadjah Mada, 2015)
Source of resistance to an Indonesia isolate of Cucumber mosaic virus (CMV-B2) in melon cultivarYamatouri has been reported. Moreover, Creb-2, a locus that confers resistance to CMV-B2 in Yamatouri hasbeen determined as a single dominant gene. To elucidate the resistance mechanism conferred by Creb-2 inmore detail, it is necessary to clone the Creb-2 gene and determine its molecular structure. One approach isby amplification and cloning of melon resistance gene analogs (MRGAs) based on degenerated PCR primersdesigned from conserved amino acids in the NBS-LRR motifs (P-loop, Kinase-2, and the GLPL) and Toll/Interleukin-1 receptor-like region (TIR). This study was aimed to identify and characterize the resistance geneanalogs from Cucumis melo L. cv. Yamatouri by employing polymerase chain reactions (PCR) as a molecularbiology tools with degenerate primers based on conserved motifs of cloned R genes. The application of molecularbiology such as DNA isolation, degenerate primers and PCR condition, cloning, sequencing, linkage analysisand mapping of resistance gene analogs to Creb-2 gene in melon will be widely discussed in this paper